PENGGUNAAN COLLINS PARSER DALAM SISTEM TANYA JAWAB BAHASA INDONESIA - Rini Sri Rahayu (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
This paper reports our work in using Collins’ parser for parsing Indonesian language. Collins’ parser using in question answering system for make a sentence which is the final answer. Question ansering system made to answer the questions directly. Used Stanford NER dan Vector Space Model for information retrieval. Trained with 500 documents, 50 questions and three type of questions. The accuracy of this system is 66%. Key wordsCollins Parser, Sistem Tanya Jawab, Stanford NER, Vector Space Model.